TALENT MANAGEMENT AND EMPLOYEE COMMITMENT IN THE HOSPITALITY INDUSTRY: A STUDY OF LE MERIDIEN HOTEL - Ollor, Helen Y.; Harry, Christina O. (BW Academic Journal, 2022)
This study titled Talent Management and Employee Commitment in Organization in the Hospitality Industry: A Study of Le Meridien Hotel, Port Harcourt. Three research Questions and Hypotheses were raised and were consisted with the objectives of the study. Relevant literatures were reviewed. Data was sourced using five Likert Questionnaire titled “Talent Management and Business Performance Questionnaire” (TM&BPQ). The study covered a population of 45 Personnel. Due to the small number of the population, the researchers decided and the entire population was used as the Sample. The Data was validated using a Committee of Experts including the Project Supervisor’s opinion. Reliability was tested using Spearman Rank Correlation Coefficient (r) which yielded 0.82. The Statistical tools used for the data analysis were Simple Percentage (%) and Chi-Square Tests. The study concluded that Talent Management of every organization must be targeted at improving Performance and that any practice in the Organization that hinders Employees Talent should be done away with. It was therefore recommended that to enhance Employees’ Innovativeness, a culture of participative leadership which also encourages bottom-up communication should be encouraged in Le Meridien Hotel, Port Harcourt and indeed, in all Hospitality Organizations. Employees should target the Development of their Organizations with their skills for Customer Needs Assessment and timely Strategic Decision making with the intention of Improving the Competitiveness of Hospitality Organizations.